Harry Potter and the order of the phoenix - Rowling, J. K. (London : Bloomsbury, 2003)
Sixth-year Hogwarts student Harry Potter gains valuable insights int o the boy Voldemort once was, even as his own world is transformed by m aturing friendships, schoolwork assistance from an unexpected source, a nd devastating losses.
Sequel to: Harry Potter and the Order of the Phoenix.
Sequel: Harry Potter and the deathly hallows.
Keywords: Potter, Harry (Fictitious character) -- Juvenile fiction; Granger, Hermione (Fictitious character) -- Juvenile fiction; Weasley, Ron (Fictitious character) -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Juvenile fiction